Pengaruh Interaksi Sosial, Kecerdasan Emosional, Fleksibilitas Kerja dan Konflik Kerja Terhadap Efektivitas Kerja Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Empat Lawang - Mardila, Mardila; Basyith, Abdul; Yusnawati, Yusnawati (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2025)
Basically, the most important thing to achieve a maximum goal is human resources (HR). Human resources are the spearhead that will be the main determinant of the success of the implementation of organizational or company activities. Independent variables in this study are Social Interaction (X1), Emotional Intelligence (X2), Work Flexibility (X3) and Work Conflict (X4) While the dependent variable is Work Effectiveness (Y). In the study, all populations were sampled as many as 35 people. The results of the study showed that social interaction, emotional intelligence, work flexibility, and work conflict have a positive and significant influence on employee work effectiveness. The combination of social interaction skills, emotional management, flexibility in adjusting to work demands, and good conflict management contribute comprehensively to increasing the work effectiveness of employees of the Financial and Regional Asset Management Agency of Empat Lawang Regency. This shows the importance of a holistic approach in human resource management to achieve optimal performance